Polymer-bound chiral auxiliaries in asymmetric hydride reductions. - Lecavalier, Pierre. (University of Ottawa (Canada), 1991)
The preparation of chiral amino alcohols which can be used in the asymmetric reduction of acetophenone is described. These amino alcohols were complexed with lithium aluminum hydride (LAH) and achiral agents in various ratios and once treated with acetophenone, afforded l-phenylethanol in poor to moderate optical yields (20%-70%). These chiral molecules were grafted to 1% crosslinked polystyrene and the polymeric hydride complexes yielded l-phenylethanol in lower optical yield than the model compounds. A detailed study of this behavior using l-ephedrine as the chiral auxiliary allowed us to conclude that site interactions as well as site accessibility were responsible for a decrease in the optical yield of the alcohol when the polymer-supported reagent was used in the reduction of the ketone. This polymer behavior is referred to as the "polymer effect". By making use of polymers with a low degree of functionalization, it was nonetheless possible to obtain optical yields comparable to that of the model molecules. Some amino alcohols were also tested as complexes of diborane and similar optical yields to those of the aluminum hydride complexes were obtained. In order to study the limitation of polymer aluminum complexes vs. the borane complexes, we attempted to prepare polymer-supported 83 and 84. Because of the lability of the benzyl ether bond, the desired polymers were not obtained in sufficiently high yield to allow their use in the reduction of acetophenone.
Keywords: Chemistry, Organic.